Evidence for a warm and humid Mid-Holocene episode in the Aegean and northern Levantine Seas (Greece, NE Mediterranean) - Triantaphyllou, M.V.; Gogou, A.; Bouloubassi, I.; Dimiza, M.; Kouli, K.; Rousakis, G.; Kotthoff, U.; Emeis, K.-C.; Papanikolaou, M.; Athanasiou, M.; Parinos, C.; Ioakim, C.; et al. (Regional Environmental Change, 2014)
Marine and terrestrial biological and biogeochemical proxies in three sediment cores from North and SE Aegean and northern Levantine Seas record continuous warm and humid conditions between 5.5 and 4.0 ka BP related to the establishment of relatively stratified conditions in the upper water column. These conditions may have resulted from the concordant albeit weak Mid-Holocene South Asian monsoon forcing, combined with lighter Etesian winds. During this interval, sea surface temperatures fluctuate in the Aegean Sea, although exhibiting a strong positive shift at*4.8 ka BP. The warm and humid climatic conditions triggered upper water column stratification and enhancement of the deep chlorophyll maximum (DCM), leading to dysoxic conditions and the deposition of a sapropel-like layer, but only in the SE Aegean site. In contrast to the shallow water SE Aegean, the deeper North Aegean and the northern Levantine sites, although experiencing stratification in the upper parts of the water column, did not achieve bottom-water dysoxia. Thus, a top–bottom mechanism of stratification–DCM development accompanied by fast transport and burial of organic matter is a likely explanation for the preservation of productivity signal in the shallow sites of the SE Aegean and establishment of sapropelic conditions during the warm and humid Mid-Holocene. The termination of the Mid-Holocene warm and humid phase coincides with the ‘‘4.2 ka’’ climate event. Our data exhibit an N–S time transgressive aridification gradient around the Aegean Sea, most probably associated with the reorganization of the general atmospheric circulation during the Mid-Holocene.